Comparison of waist-height ratio and other obesity indices in the prediction of diabetic peripheral neuropathy - Lawal, Yakubu; Mshelia-Reng, Rifkatu; Omonua, Special O.; Odumodu, Kenechukwu; Shuaibu, Ramatu; Itanyi, Ukamaka D.; Abubakar, Amina I.; Kolade-Yunusa, Hadijat O.; Songden, Zumnan D.; Ehusani, Caleb O.; Adediran, Olufemi; Anumah, Felicia E. (Frontiers in Nutrition, 2022)
Background Waist-height ratio (WHtR) is increasingly being studied as a simple and effective measure of central obesity. Reports have shown that WHtR is a better predictor of hypertension, diabetes, and cardiovascular diseases when compared to traditional obesity indices like body mass index, waist circumference, and waist-hip ratio. This study is therefore, aimed at comparing WHtR with other obesity indices in the prediction of peripheral neuropathy in persons with diabetes mellitus (DM). Methodology One thousand and forty (1040) persons with DM were enrolled following consent. Relevant details of history were obtained, followed by physical examinations. Data was analyzed using IBM-SPSS version 23. Logistic regression was used to compare the odds ratio of obesity indices in the prediction of peripheral neuropathy. Level of significance used was p < 0.05. Results Logistic regression showed that WHtR had the highest odds ratio (OR) for the prediction of peripheral neuropathy (OR 9.11, 95% CI 3.07-47.97, p=0.002), followed by WC (OR 2.01, 95% CI 1.09-4.05, p=0.004), and BMI (OR 1.26, 95% CI 1.00-3.99, p=0.019). Conclusion Waist-height ratio has the highest odds ratio in the prediction of diabetic peripheral neuropathy in both genders, followed by waist circumference in the males, and body mass index in the females.